The Indonesian version of the Short Grit Scale (Indonesian Grit-S): Psychometric Properties Based on the Multidimensional Rasch Model - Nursalam, Nursalam; Bintang, Rahmat S.; Zainuddin, Kurniati; Mutiah, Diana (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2025)
“Grit” refers to persistence in trying and consistent interest in achieving long-term goals. The Short Grit Scale (Grit-S) is one of the measures used to assess grit. Given that previous research on the Grit-S scale was reported with a CFA approach, this study aims to examine the psychometric properties of the Indonesian Grit-S using Rasch model analysis. Rasch model shows a more detailed analysis than CFA by explaining item difficulty, item fit statistics, reliability, and wright map. Participants in the study were 480 students (male: 86 and female: 394) with an age range of 17-25 years (mean age: 20.05, SD age: 1.32). The sampling method used was non-probability sampling with a convenience sampling technique. The research analysis results show that the Indonesian Grit-S has a good reliability. In addition, all Indonesian Grit-S scale items fit using the Rasch model. Overall, the results showed that the Indonesian Grit-S scale has valid and reliable psychometric properties and can be used to measure grit.